KETIDAKEFEKTIFAN KALIMAT DALAM BUKU AJAR TEMATIK KELAS SATU SEKOLAH DASAR (The Uneffecetive Sentences found in Grade One Theme Textbook at Elementary School) - NFN Lismelinda (Balai Bahasa Sumatra Barat, 2017)
AbstractThe purpose of this paper is to describe the uneffective sentences found in the textbooks forgrade one at elementary school. This paper uses qualitative descriptive method. Based on theresults of the discussion there is an error in writing effective sentences in the textbook. Theerrors include sentence writing errors that are inconsistent with the grammatical features ofeffective sentences and dictical features of effective sentences. The non-programmaticscontained in the sentences of the first theme textbook for grade one of elementary school aremorphologically and non-programmatically syntactic. While the error that does not fit withthe dictical feature of the effective sentence is the error of diction usage. Such errors includeimprecision of diction and uncommon diction. AbstrakTujuan penulisan artikel ini adalah untuk mendeskripsikan ketidakefektifan kalimat dalam buku ajartema 1 kelas satu sekolah dasar. Tulisan ini menggunakan metode deskriptif kualitatif. Berdasarkanhasil pembahasan terdapat kesalahan dalam penulisan kalimat efektif dalam buku ajar tersebut.Kesalahan itu meliputi kesalahan penulisan kalimat yang tidak sesuai dengan ciri gramatikal kalimatefektif dan ciri diktis kalimat efektif. Ketidakgramatikalan yang terdapat dalam kalimat pada bukuajar tema 1 kelas satu sekolah dasar adalah ketidakgramtikalan secara morfologis danketidakgramatikalan secara sintaksis. Sedangkan kesalahan yang tidak sesuai dengan ciri diktiskalimat efektif adalah kesalahan penggunaan diksi. Kesalahan tersebut meliputi ketidaktepatan diksidan ketidaklaziman diksi.Kata kunci: kalimat efektif, ciri gramatikal, dan ciri diktis.